Arms for uncertainty nuclear weapons in US and Russian security policy - Cimbala, Stephen J. (Ashgate Publishing Company, 2013)
This is the most comprehensive view of nuclear weapons policy and strategy currently available. The author's division of the nuclear issue into the three ages is a never seen before analytical construct. With President Obama reelected, the reduction and even elimination of nuclear weapons will now rise to the top of the agenda once more.